Я вышла замуж в Америку: [роман] / Татьяна Успенская - Успенская Татьяна Львовна (Женские судьбы, 1997)
Экземпляры: ф.18 (2000) / Инвентарный номер: 41832 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: У 77 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44